2016
DOI: 10.3171/2015.6.peds14708
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative imaging for detection of recurrent arteriovenous malformations in children

Abstract: OBJECT The optimal method for detecting recurrent arteriovenous malformations (AVMs) in children is unknown. An inherent preference exists for MR angiography (MRA) surveillance rather than arteriography. The validity of this strategy is uncertain. METHODS A retrospective chart review was performed on pediatric patients treated for cerebral AVMs at a single institution from 1998 to 2012. Patients with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…446 In all cases, long-term follow-up, including posttreatment DSA, is critical because recurrence rates are as high as 11%. 447,448 Typically, a perioperative and 1-year postoperative DSA may be considered, followed by MRI/MRA annually for up to 5 years. 439,441,448 Arteriovenous Fistula Imaging.…”
Section: Genetic Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…446 In all cases, long-term follow-up, including posttreatment DSA, is critical because recurrence rates are as high as 11%. 447,448 Typically, a perioperative and 1-year postoperative DSA may be considered, followed by MRI/MRA annually for up to 5 years. 439,441,448 Arteriovenous Fistula Imaging.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…447,448 Typically, a perioperative and 1-year postoperative DSA may be considered, followed by MRI/MRA annually for up to 5 years. 439,441,448 Arteriovenous Fistula Imaging. MRI and MRA are useful in the evaluation of AVFs but have limitations.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…However, Morgenstern et al showed that digital subtraction angiography (DSA) is more sensitive than MRI in detecting AVM recurrence and recommended DSA at 1, 3, and 5 years postresection and every 5 years thereafter. 25 Other groups have reported cases in which MRI may have missed subtle AVM recurrences. 5 While DSA may be more sensitive in detecting AVM recurrence, 1,5,21 MRI has successfully detected asymptomatic recurrences in several documented cases in which results suggestive of AVM recurrence were often followed up with DSA.…”
Section: Discussionmentioning
confidence: 99%
“…They carry an annual risk of hemorrhage of approximately 3.2%, a 5–10% mortality rate, and a 50% risk of neurological morbidity. [ 4 23 ] The large majority of AVMS are clearly evident on DSA, although several authors dating back several decades have described angiographically “occult” AVMs that were obscured following rupture. [ 24 27 ] Hypotheses for this phenomenon include possible lesional thrombosis, compressive occlusion of lesion from hematoma, transient vasospasm, or small nidus.…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%
“…AVMs in children are fraught with a high recurrence rate (as high as 14%),[ 23 ] especially in lesions with a diffuse nidus[ 15 ] or deep venous drainage. There are no definitive guidelines for postoperative surveillance, however, undoubtedly, DSA has the highest resolution and sensitivity.…”
Section: Arteriovenous Malformationsmentioning
confidence: 99%